New technology to improve the recovery of fine particles in froth flotation based on using hydrophobized glass bubbles. (1st September 2020) - Arriagada, S.; Acuña, C.; Vera, M.
Highlights: A new technology to improve the selective recovery of fine particles was developed. The technology is based on using hydrophobized glass bubbles (HGB) as carrier of fines. Flotation tests were conducted to evaluate the effect of using HGB. HGB improved the flotation kinetics and the grade-recovery curve of fines. No frother addition was needed when HGB were used. Abstract: A new technology has been developed to improve the selective recovery of fine particles in the froth flotation process. The technology is based on using hydrophobized glass bubbles (HGB) as a carrier material for hydrophobic fine particles, which promotes selective particle agglomeration. A proof of concept was carried out using fine graphite particles (13 µm) in order to validate the technology. The results showed that HGB can collect fine, hydrophobic particles, forming particle aggregates of larger size. Batch flotation kinetics tests were also conducted to quantify the effect of using HGB in the flotation metallurgical performance of a finely ground copper ore (d80 = 12 µm). The results indicated that HGB addition increased the flotation kinetics rate constant by 1.4 times and the maximum attainable recovery from 64% up to 90% (considering a first-order kinetics model). The grade-recovery and selectivity curves are shifted positively using HGB. In conclusion, the use of HGB technology in the froth flotation process presents a significantly improved metallurgical performance and process selectivity, becoming an alternative to face the challenge of recovering fine particles.